Assessing the situation of Zahedan city in accordance with indicators of the creative city - Ali Rahimi; Abdolbaset Darzadeh Mehr; Roghayeh Mirzaei; Maliha Shah Beyki (Sustainable Earth Trends)
The world today is transitioning from the industrial age to the creative age. In addition to meeting basic needs, the creative age seeks to meet their creative needs such as the need for imagination, mastery, vitality, innovation and curiosity. In such an urban city, with an emphasis on elites and urban planning specialists, urban planners and other related sciences, cities become attractive places to study, work and preserve urban elites, and by improving the quality of universities and scientific centers, quality of work, life quality, tolerance and lifestyle can move in this direction. In this regard, the present article has evaluated and analyzed the indicators of the creative city in the Zahedan. The research method is descriptive-analytical and its type is applied-developmental. Information was collected in both documentary and survey forms (questionnaire and interview). The statistical population of the study is the population of Zahedan is 672589 people and using Cochran's formula, the sample size is calculated as 324 people and the data were analyzed using factor analysis tests and Pearson correlation coefficient with SPSS statistical software.